Manajemen Referensi dengan Aplikasi Zotero - Muhammad Kasim Aidid; M. Nadjib Bustan; Ruliana Ruliana (DEDIKASI, 2020)
Based on the situation analysis, a Community Partnership Program (PKM) activity is proposed to train the use of reference management software for teachers in which SMA Negeri 4 Pinrang Regency is the partner. The identified problems are: (1) Lack of skills in using reference manager software, (2) Zotero as open source software is unknown, (3) The need for the ability to use reference manager software that can be applied in writing scientific papers. The material is presented through zoom meetings in plenary and in groups according to the schedule. In the plenary presentation of the material, material on basic concepts in research and writing of scientific papers was presented then continued with the provision of material on the use of Zotero in writing scientific articles. Some of the requirements to become a participant are: (1) having an interest in learning the basic concepts of reference management, (2) having never attended a similar training. (3) must attend all training activities. From the PKM activities that have been carried out as well as the team's internal survey, it can be concluded that in the implementation of this activity: (1) Participants become literate and skilled in operating the Zotero software, (2) The Zotero menu is well known to PKM participants, (3) Participants have the ability to use Zotero in writing scientific articles.